Fruitable / Nelly Stephanie Nawari ... [et al.] - Nawari, Nelly Stephanie; Jose, Angelina; Balalang, Susuze; Fook Phen, Fenniecia (2015)
Fruitable is a food & beverage kiosk located at Imago shopping complex in time square Kota Kinabalu, Sabah to attract people since Imago is new shopping complex. Fruitable provide F&D to all the ages level. Fruitable also accepts order for event wedding,birthday,engagement or others. Fruitable can serve all customer nicely. While there are many F&B in market like Fruitable. Fruitable will make a differences in tenn of product. We are provide F&D focuses more to healthy. Through serve a healthy product,fruitable will slowly but surely will gain a large of market. People will consume our product when they realize that how important to take care of their health. Nowadays they are Jot of company produce unhealthy product therefore Fruitable has foreseen the opportunity to provide the finest and highest quality to decrease the healthy problem among Malaysian.This has shown that Fruitable has caliber to be one of the successfully F & B product in Malaysia and worldwide one day. We,Fruitable,saw the opportunity that this business has the potential of success of provide that it is handled efficiently. People consume food and drinks in their life to continue their life. Fruitable sees this as a way to prosper in this market,by taking advantages of all these people's need.